PENGARUH METODE BERCERITA BERBANTUAN WAYANG KERTAS TERHADAP KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN - virna Choirin Nisa; Dewi Komalasari; Kartika Rinakit Adhe; Muhammad Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking ability is an important aspect of early childhood language development that needs to be optimally stimulated through engaging and meaningful learning activities. However, based on field observations, some children aged 4–5 years still experience difficulties in expressing ideas, constructing simple sentences, and interacting verbally with teachers and peers. This study aimed to analyze the effect of storytelling using paper puppet media on the speaking ability of children aged 4–5 years at TK Utsman bin Affan Surabaya. This study employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The research subjects consisted of 30 children divided into an experimental group and a control group. Data were collected using an observation sheet to assess children’s speaking ability, while data analysis was conducted using SPSS, including tests of normality, homogeneity, and hypothesis testing. The results showed that there was a greater improvement in speaking ability in the experimental group compared to the control group after the treatment was applied. Children in the experimental group demonstrated better development in expressing ideas confidently, using more varied vocabulary, constructing simple sentences, and engaging in verbal interactions. The findings indicate that storytelling assisted by paper puppet media can be utilized by early childhood education teachers as an innovative and enjoyable learning strategy to optimally stimulate children’s speaking ability